THEORETICAL ASPECTS OF FORMATION OF COGNITIVE ACTIVITY OF STUDENTS BY MEANS OF NEW COMPUTER TECHNOLOGIES - N.A. Ovcharenko; O.S. Ovcharenko (Academy of Cognitive and Natural Sciences, 2009)
The questions, which concerning of theoretical aspects of the forming of cognitive activity of personalities are considered in this article. The possibilites and categorization of new computer technology are revealed in the context of the forming the activities to cognitionю